Survey of Shooting Accuracy Level and Foot Eye Coordination of Futsal Players of SMKN 3 Takalar - Azis, Ilham; Syamsuddin, Syachrul (SHOOTING: Journal of Sport, Health, and Education, 2024)
The purpose of this study was to determine the level of shooting accuracy and eye-foot coordination of futsal players at SMKN 3 Takalar. This study is a quantitative descriptive study, which intends to describe or provide an overview of the level of shooting accuracy and eye-foot coordination of futsal players at SMKN 3 Takalar. The population in this study were 20 futsal players at SMKN 3 Takalar and the sample of this study was all futsal players at SMKN 3 Takalar. The data analysis technique in this study used Descriptive Test and Percentage Test. Based on data analysis, the results of the descriptive test of the level of shooting accuracy of futsal players at SMKN 3 Takalar obtained a minimum score of = 12, maximum score = 31, SUM = 225, range = 19, standard deviation = 5.259. The results of the descriptive test of the foot-eye coordination of futsal players at SMKN 3 Takalar obtained a minimum score of = 6, a maximum score of = 13, SUM = 100, range = 7, standard deviation of = 2.498. Based on the results of the percentage test of the shooting accuracy of futsal players at SMKN 3 Takalar, the results were obtained in the very good category, there were 0 people with a percentage of 0%, in the good category there were 1 person with a percentage of 8%, in the sufficient category there were 2 people with a percentage of 17%, in the less category there were 9 people with a percentage of 75% in the very less category there were 0 people with a percentage of 0%. The results of the percentage test of the foot-eye coordination test obtained results in the very good category, there were 3 people with a percentage of 25%, in the good category there were 3 people with a percentage of 25% in the low category there were 0 people with a percentage of 0% in the very low category there were 0 people with a percentage of 0%. Based on the results of the analysis above, it is concluded that the shooting accuracy level of futsal players at SMKN 3 Takalar is in the less category and the eye-foot coordination of futsal players at SMKN 3 Takalar is in the Medium category